Pancasila Dan Negara Kesatuan Republik Indonesia; Aktualisasi Subyektif Nilai-Nilai Pancasila Solusi Berbangsa dan Bernegara - Rahma, Jihan Nadia (BULETIN ADALAH, 2021)
The subjective actualization of Pancasila values is the implementation of Pancasila values in all Indonesian citizens. The important position of Subjective actualization of Pancasila values in the life of the nation and state is that the application of the concept of objective actualization is based on subjective actualization of each person of the Indonesian nation so that objective actualization of Pancasila values will be easier too carry out and also the problems that arise. Chronic and acute conditions can be handled easily and even prevented so that they do not multiply into the main problem that divides the nation and state of  Indonesia. The disintegration and implementation of Pancasila values is one way out of the nation’s ideology will be safe but to achieve the level of ideological security a process is needed to achieve the actualization. Ttherefore, the actualization of Pancasila is needed helping the smooth of life of the nation and state.